Peran Pet Attachment Terhadap Kebahagiaan Pemilik Hewan Peliharaan Di Kota Banjarmasin - Tribudiman, Arief; Rahmadi, Rahmadi; Fadhila, Mahdia (Islamic Psychology Study Program, Faculty of Ushluddin and Humanities, UIN Antasari Banj, 2020)
Keeping animals, especially cats, has been demonstrated by the Prophet. This certainly saves goodness in it. If you see the relationship between humans and animals that are intertwined in a longer period of time will cause attachment in it or we call it a pet attachment. So the purpose of this study will look at how the role of pet attachments on the happiness of pet owners. This research is a field research, with a qualitative descriptive approach. The technique of selecting research subjects using purposive sampling technique, the number of samples as many as 22 people and after screening tests using a stickiness scale that has been validated and reliable (0.807), obtained 5 people included in the category. Furthermore, 2 subjects who were willing to take part in the research. Data collection used was semi-structured interviews, non-participant observation, and documentation. The results showed a description of pet attachments in pet owners including physical contact, selection criteria, reactions to separation and loss, effects on physical and psychological health. The description of the happiness of pet owners can be seen in the aspects of happiness, which consists of aspects of positive emotion, engagement, positive relationships, meaning and accomplishment. All aspects are fulfilled from the attachment to the pet (pet attachment), causing happiness to the pet owner.